MicroRNAs in the Regulation of NADPH Oxidases in Vascular Diabetic and Ischemic Pathologies: A Case for Alternate Inhibitory Strategies? - Sean R. Wallace; Patrick J. Pagano; Damir Kračun (MDPI AG, 2022)
Since their discovery in the vasculature, different NADPH oxidase (NOX) isoforms have been associated with numerous complex vascular processes such as endothelial dysfunction, vascular inflammation, arterial remodeling, and dyslipidemia. In turn, these often underlie cardiovascular and metabolic pathologies including diabetes mellitus type II, cardiomyopathy, systemic and pulmonary hypertension and atherosclerosis. Increasing attention has been directed toward miRNA involvement in type II diabetes mellitus and its cardiovascular and metabolic co-morbidities in the search for predictive and stratifying biomarkers and therapeutic targets. Owing to the challenges of generating isoform-selective NOX inhibitors (NOXi), the development of specific NOXis suitable for therapeutic purposes has been hindered. In that vein, differential regulation of specific NOX isoforms by a particular miRNA or combina-tion thereof could at some point become a reasonable approach for therapeutic targeting under some circumstances. Whereas administration of miRNAs chronically, or even acutely, to patients poses its own set of difficulties, miRNA-mediated regulation of NOXs in the vasculature is worth surveying. In this review, a distinct focus on the role of miRNAs in the regulation of NOXs was made in the context of type II diabetes mellitus and ischemic injury models.